The Analysis of English Used in Bali Tour and Travel Agencies’ Correspondences - Ni Made Ayu Sulasmini; I Nengah Sudipa; I Wayan Simplen; Made Sri Satyawati (ITScience (Information Technology and Science), 2023)
English delivers various functions in the realms of tourism and hospitality. Since the significant role of English in tourism business, the talents working in the sector should be fluently communicating in English. One sector requires fluent English skill in tour and travel agencies which driving to the English course for students of tour and travel business. This study aimed at finding out the use of English in tour and travel agencies’ correspondences as well as analysing the language functions found in the correspondence. The research implemented qualitative research approach in which the data were collected through interview and observation in BBM tour and travel. Data were analysed qualitatively to describe and explain the data clearly and systematically. The results of data analysis revealed that English is used to do correspondences to clients and partners. The topics covered in the correspondences were offering package, tour booking, general inquiry, booking cancelation, inspection proposal, commission agreement, contract rate request, collection letter, and acknowledgement letter. The English used to deliver those topics was falling into four language functions, based on Leech’s theory, that were phatic function, informative function, directive function, and expressive function. Meanwhile aesthetic function was not notably found in the correspondence since the communication done by tour and travel agencies should be clear and understandable. The results of this research significantly contribute to the English education, particularly in tour and travel business.